As múltiplas faces do desenvolvimento rural: compreendendo as experiências de transição agroecológica nos municípios de Santa Cruz da Baixa Verde e de São Lourenço da Mata, Pe - Lima, Filipe Augusto Xavier (2016)
Since the development of Technical Assistance and Rural Extension National Policy (Pnater) in 2004, it can be observed that subsequent extension policies shows both theoretical and methodological ambiguities, distortions and weaknesses, with regard to Agroecological approaches and sustainable rural development strategies, which might lead to damages and uncertainties regarding extension actions, as well as among family farmers, public that benefits from technical assistance and public extension politics. Given the importance of this theme, the research poses the following question: how Agroecology has been incorporated to rural development dynamics, respecting a wide range of socioeconomic, productive and environmental situations, as well as associative organizations, which shape strategies and experience of family farmers? The work aims to analyze how different situations influence rural development. Respecting this, the research consists on a comparative analysis between two specific cases from Pernambuco state: a family farmers group from Santa Cruz da BaixaVerde which experienced an agroecological transition process in 1990s, and a group of farmers settled through agrarian reform at São Lourenço da Mata, which participated of an agroecological transition process, starting in the late 2000s. With regard to methodological resources, the thesis will be guided in the mixed model, which enables integration between qualitative and quantitative approaches, following some additional steps, such as literature, documentary research, case study, direct observation, survey and data processing. The comparative approach between two case studies, enabled the observation of actor´s participation on construction of qualitative factors which compound sustainability of rural development strategies and experiences driven by Agroecology. Moreover, it was clear that such as the selection of appropriate strategies for sustainable rural development, also the ability to readapt itto scenery changes and to learn from others' experiences are crucial in the long run, regarding the success of this kind of initiative. Considering that agroecological transition is permanently subjected to re-orientations, this research shows how actors and social networks can influence rural development; and which factors might lead to qualitative differences among individual cases; and which factors may lead to more or less sustainable dynamics in a time spam. The importance of this research is justified by the possibility of enabling the comprehension of relationship between family farmers in agroecological and other social stakeholders, revealing singularities of rural development. In addition, an analysis that confronts particularities of rural development strategies in different local contexts, as well as its consequences, might contribute to the improvement of technical assistance and rural extension policies towards family farmers.